Inteligencia artificial en las finanzas: una revisión bibliográfica - G, Jyothi (2025)
In every aspect of the financial industry—from decision-making to risk management, fraud detection and customer service—artificial intelligence (AI) is causing significant changes. This paper reviews the application of AI in finance and is based on more than 40 Scopus-indexed articles which provide some fresh insight. With the help of advanced machine learning and deep learning algorithms, banks are achieving unprecedented levels of efficiency and personalized service. This research looks at major AI applications, bringing into focus their potential role in strategic decision-making and risk assessment. However, it also critically analyses key challenges, such as data privacy issues, how to explain models under scrutiny from humans (i.e., theoretically impossible), and ethical considerations attached to AI's implementation. The evolution of AI technologies creates not only disruptive opportunities but also complex regulatory issues for financial services. By compiling the findings of the present research, this review gives a comprehensive description of how AI is remoulding the field of finance and offering directions for what comes next.